Efficacy of tarsal immobilization to alleviate Achilles tendon strain in vivo – direct measurements via a differential variable reluctance transducer™ (DVRT) strain gauge in a canine model - Lister, Stephanie A. (Kansas State University, 2008)
Objective: To measure strain in vivo in the calcanean tendon during trotting in canines, and to compare to strain present after tibiotarsal immobilization. Animals: 6 canines Procedures: A Differential Variable Reluctance Transducer[superscript]TM (DVRT®) strain gauge was surgically implanted on the common gastrocnemius tendon. Surface EMG, % strain, and ground reaction forces were measured prior to intervention and after immobilization. Peak vertical force (Fz), vertical impulse, initial, maximum and final strain, and peak-to-peak EMG amplitude were recorded. Data was analyzed using repeated measures analysis of variance and paired t-tests (p[equal to or less than]0.05). Results: Timing of strain data correlated closely to the hind limb footstrike and EMG activity in all dogs. Maximum tendon strain occurred simultaneous with peak Fz. Continued muscle contraction was evident after immobilization. There was no statistical difference in maximum strain after immobilization compared to normal motion. Minimum strain, both at the beginning and end of the strain curve, was significantly decreased with the immobilized state compared to non-immobilized joints. Conclusions and Clinical Relevance: Tibiotarsal immobilization did not eliminate calcaneal tendon strain during weight bearing. Decreased isometric muscle contraction during swing phase of the gait would account for smaller minimum strain in immobilized joints. Immobilization is frequently applied after Achilles tendon rupture to alleviate strain and force on the sutured repair, with possible complications due to the immobilization method. Direct correlation of strain with tendon force was not made in this study. This would be an important factor before adjusting current treatment recommendations.
Keywords: Calcaneal tendon; Tendon strain; Immobilization; Biology, Veterinary Science (0778)